Kesusastraan Kontemporer Cina: Kontemporeritas dan Kebijakan Pemerintah - Wuryandari, Nurni W. (UI Scholars Hub, 2006)
What is meant by contemporary literature? The first thing that comes up in mind is that the terminology of contemporary literature points out to